2008
DOI: 10.1007/s00109-008-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical findings and their correlations in Silver-Russell syndrome: implications for a positive role of IGF2 in growth determination and differential imprinting regulation of the IGF2–H19 domain in bodies and placentas

Abstract: Silver-Russell syndrome (SRS) is characterized by growth failure and dysmorphic features and is frequently caused by hypomethylation (epimutation) of the H19-DMR. Although molecular and clinical studies have extensively been performed for SRS patients themselves, such studies have not been carried out for placentas. We identified 20 epimutation-positive and 40 epimutation-negative Japanese SRS patients and obtained placental weight data from 12 epimutation-positive and ten epimutation-negative patients and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 37 publications
6
48
1
1
Order By: Relevance
“…In a mouse model in which H19 was deleted and Igf2 expression was increased, both the placenta and the fetus were overgrown at E19 (35,36). In humans, placental growth defects are common in individuals with BWS and SRS (24,37). We observed that H19 +/hIC1 placentas not only are smaller, but also have abnormal placental morphology.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In a mouse model in which H19 was deleted and Igf2 expression was increased, both the placenta and the fetus were overgrown at E19 (35,36). In humans, placental growth defects are common in individuals with BWS and SRS (24,37). We observed that H19 +/hIC1 placentas not only are smaller, but also have abnormal placental morphology.…”
Section: Resultsmentioning
confidence: 65%
“…Because H19 +/hIC1 embryos display similar phenotypes to those of many patients with SRS who present with IC1 hypomethylation, including altered H19 and Igf2 expression and growth defects (23,24), we hypothesized that these embryos can serve as a model for SRS. Placental growth defects are prevalent among individuals with SRS (24); thus, we further characterized H19 +/hIC1 placentas to study potential mechanisms underlying SRS associated with IC1 hypomethylation.…”
Section: Resultsmentioning
confidence: 99%
“…46 Epigenetic abnormalities are detected in up to 35-65% of patients, the most frequent one being hypomethylation of the H19 ICR (Table 1). [46][47][48][49][50][51][52] Like BWS cases, a proportion of patients with Silver-Russell syndrome show hypomethylation at multiple ICRs (Table 1). 43,53 Moreover, over two-third of such patients have hypomethylation not only at the maternally methylated ICRs but also at another paternally methylated ICR at the DLK1-MEG3 locus (IG-DMR) ( Table 1).…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
“…We first performed bisulfite sequencing for the H19-DMR (differentially methylated region) and KvDMR1 as a screening of BWS 11,12 and that for the IG-DMR and the MEG3-DMR as a screening of upd (14)pat, 10 using leukocyte genomic DNA. Paternally derived clones were predominantly identified for the four DMRs examined ( Figure 1a).…”
Section: Methylation Analysismentioning
confidence: 99%